Familiar Stranger: An Introduction to Jesus of Nazareth (Teaching theology and religion, 2006)
Books reviewed: McClymond, Michael L., Familiar Stranger: An Introduction to Jesus of Nazareth Reviewed by Roger P. Ebertz University of Dubuque